Optically responsive supramolecular polymer glasses - Balkenende, Diederik W. R. (Nat Commun, 2016)
The reversible and dynamic nature of non-covalent interactions between the constituting building blocks renders many supramolecular polymers stimuli-responsive. This was previously exploited to create thermally and optically healable polymers, but it proved challenging to achieve high stiffness and good healability. Here we present a glass-forming supramolecular material that is based on a trifunctional low-molecular-weight monomer ((UPyU)(3)TMP). Carrying three ureido-4-pyrimidinone (UPy) groups, (UPyU)(3)TMP forms a dynamic supramolecular polymer network, whose properties are governed by its cross-linked architecture and the large content of the binding motif. This design promotes the formation of a disordered glass, which, in spite of the low molecular weight of the building block, displays typical polymeric behaviour. The material exhibits a high stiffness and offers excellent coating and adhesive properties. On account of reversible dissociation and the formation of a low-viscosity liquid upon irradiation with ultraviolet light, rapid optical healing as well as (de)bonding on demand is possible.